Dissenting Opinion in Judges' Decisions Linked to The Principle of Justice - Eti Koerniati (Fakultas Hukum, Universitas Islam Bandung, 2022)
Judge's decision-making often invites problems because it is considered less transparent and justice seekers often question accountability issues besides the extent of their position in influencing sanctions in determining verdicts. This study aims to analyze the implementation of the effect of dissenting opinion on determining the weight of sanctions in making transparent judge decisions and determining the position of dissenting opinions in making rational judge decisions in the context of strengthening transparency and fair accountability. This research method uses a normative juridical approach that analyzes secondary data and with qualitative analysis techniques that produce conclusions. The results showed that the implementation of the inclusion of dissenting opinions in the formulation of judge's decision-making encountered various problems such as the varying quality of judges' abilities, the problem of guaranteeing the safety of judges, the culture of seniority so that it had little influence on the severity of the sanctions (strafmaat) that the defendant had to accept. The position of dissenting opinion in making transparent and accountable judge decisions is a means for judges to assess and explore case material with their own knowledge so that the public can evaluate the decision (exst-post). The inclusion of different opinions from minority judges in the decision is useful as a reference material for justice seekers (justitiabelen) if they are not satisfied with the decision to take legal action and put these different opinions into the memory of appeal/cassation so that the correction curve for the decision is quite large.